Clinical translation of targeted α-therapy: an evolution or a revolution? - Feuerecker, Benedikt; Kratochwil, Clemens; Ahmadzadehfar, Hojjat; Morgenstern, Alfred; Eiber, Matthias; Herrmann, Ken; Pomykala, Kelsey L. (Journal of nuclear medicine, 2023)
The field of radioligand therapy has advanced greatly in recent years, driven largely by β-emitting therapies targeting somatostatin receptor-expressing tumors and the prostate-specific membrane antigen. Now, more clinical trials are under way to evaluate α-emitting targeted therapies as potential next-generation theranostics with even higher efficacy due to their high linear energy and short range in human tissues. In this review, we summarize the important studies ranging from the first Food and Drug Administration-approved α-therapy, 223Ra-dichloride, for treatment of bone metastases in castration-resistant prostate cancer, including concepts in clinical translation such as targeted α-peptide receptor radiotherapy and 225Ac-PSMA-617 for treatment of prostate cancer, innovative therapeutic models evaluating new targets, and combination therapies. Targeted α-therapy is one of the most promising fields in novel targeted cancer therapy, with several early- and late-stage clinical trials for neuroendocrine tumors and metastatic prostate cancer already in progress, along with significant interest and investment in additional early-phase studies. Together, these studies will help us understand the short- and long-term toxicity of targeted α-therapy and potentially identify suitable therapeutic combination partners.
Online veröffentlicht: 28. April 2023
Gesehen am 03.08.2023